Continuum damage modeling and progressive failure analysis of carbon fiber/epoxy composite pressure vessel. (15th December 2015) - Wang, Liang; Zheng, Chuanxiang; Luo, Hongying; Wei, Shuang; Wei, Zongxin
Abstract: This paper presents a progressive damage model, which is sufficiently general to predict the ultimate load-bearing ability and complex failure behaviors of the aluminum–carbon fiber/epoxy composite vessel structure. The model is implemented in the commercial finite element software ABAQUS based on the integration of material property degradation method (MPDM) and cohesive element (CE) method. The MPDM is implemented by ABAQUS user subroutine UMAT to model the intralaminar failure of composite laminates, while CEs are employed to simulate the delamination initiation and evolution at the interfaces. The progression of damage is controlled by a linear damage evolution law, which is based on the fracture energy dissipating during the process. In addition, the predictions of the model are also compared with experiments and reasonably good agreements are obtained.